2020
DOI: 10.3847/1538-4357/ab9745
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of 44Ti and 56Ni Production in Core-collapse Supernova Shock-driven Nucleosynthesis to Nuclear Reaction Rate Variations

Abstract: Recent observational advances have enabled high resolution mapping of 44Ti in core-collapse supernova (CCSN) remnants. Comparisons between observations and models provide stringent constraints on the CCSN mechanism. However, past work has identified several uncertain nuclear reaction rates that influence 44Ti and 56Ni production in postprocessing model calculations. We evolved one-dimensional models of 15 M ⊙, 18 M ⊙, 22 M ⊙, and 25 M ⊙ st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…The 44 Ti(α, p) 47 V, 40 Ca(α, γ) 44 Ti, 40 Ca(α, p) 43 Sc, 17 F(α, p) 20 Ne, and 21 Na(α, p) 24 Mg reactions were identified by Magkotsios et al [10] as affecting 44 Ti and 56 Ni production. On the other hand, Subedi, Meisel, and Merz [55] identified 13 N(α, p) 16 O, 17 F(α, p) 20 Ne, 52 Fe(α, p) 55 Co, 56 Ni(α, p) 59 Cu, and 39 K(p, α) 36 Ar as some of the most important α-cluster reactions. While studies do not always agree on the most important reactions to constrain, it is clear that α-clusterized nuclei are important for nucleosynthesis in CCSN.…”
Section: Figure 9 (A)mentioning
confidence: 99%
“…The 44 Ti(α, p) 47 V, 40 Ca(α, γ) 44 Ti, 40 Ca(α, p) 43 Sc, 17 F(α, p) 20 Ne, and 21 Na(α, p) 24 Mg reactions were identified by Magkotsios et al [10] as affecting 44 Ti and 56 Ni production. On the other hand, Subedi, Meisel, and Merz [55] identified 13 N(α, p) 16 O, 17 F(α, p) 20 Ne, 52 Fe(α, p) 55 Co, 56 Ni(α, p) 59 Cu, and 39 K(p, α) 36 Ar as some of the most important α-cluster reactions. While studies do not always agree on the most important reactions to constrain, it is clear that α-clusterized nuclei are important for nucleosynthesis in CCSN.…”
Section: Figure 9 (A)mentioning
confidence: 99%
“…Recent sensitivity studies of core-collapse supernovae (CCSNe) to nuclear reaction rates showed that the 59 Cu(p,α) 56 Ni and 59 Cu(p,γ) 60 Zn reaction rate variations notably affect the production of γ-ray emitting isotopes (Hermansen et al 2020;Subedi et al 2020). As CCSNe also accompany the rp process, the NiCu cycle or individual reactions can affect the CCSNe model predictions.…”
Section: Conclusion and Remaining Workmentioning
confidence: 99%
“…A large number of nuclear reactions affect the production of these isotopes and precise knowledge of nuclear reaction rates are needed to constrain astrophysical models and to obtain accurate information about the CCSN. A recent sensitivity study was performed by Subedi et al [1], in which the rates of various reactions were varied and their impact on the synthesis of 44 Ti and 56 Ni isotopes were inferred. In these calculations, a 1-D model was evolved for 15 ∼ M , 18 ∼ M and 22 ∼ M progenitor stars from zero-age main sequence through the explosion.…”
Section: Introductionmentioning
confidence: 99%